The Effect of Product Quality, Brand Image and Brand Trust on Purchase Decision of Wardah Cosmetics in Jakarta National University - Arlisa Nurul Imani; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of Product Quality, Brand Image and Brand Trust on Purchase Decision of Wardah Cosmetics in Jakarta National University Students. The population of this research is the students of the National University of Jakarta who used Wardah cosmetics products. The sampling method used in this study was purposive sampling. The sampling method used purposive sampling technique, the number of samples was 100 respondents with the sample criteria being jakarta National University students who had purchased and used Wardah cosmetics. This type of data uses primary data in the form of a questionnaire. This study uses analytical techniques including multiple linear regression tests, and hypothesis testing with the help of SPSS 25. Partially, product quality has a positive and significant effect on Wardah cosmetic purchasing decisions for students at the National University of Jakarta this is indicated by the results of the t-test with the acquisition tcount>ttable (2,057>1,984) and sig value (0,042<0,05), brand image has a positive and significant effect on purchasing decisions for Wardah cosmetics for students at National University of Jakarta as evidenced by the t-test results with the acquisition of tcount>ttable (2,481>1,984) and the sig value (0,015<0,05), and brand trust has a positive and significant effect on purchasing decisions for Wardah cosmetics. at the Jakarta National University Students as evidenced by the t-test results with the acquisition of tcount>ttable (2,116>1,984) and sig value (0,037<0,05)